Motilities and viabilities of separation results of spermatozoa X and Y technique of anode-cathode by in vitro - Musanip Musanip (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Spermatozoa X and Y have different characteristics. Various techniques have been developed to exploit some differences to dissociate spermatozoa carriers of chromosomes X and Y. Technique with cathode-anode in vitro can be expected to be more practical, cheap, easy, and efficient compared to other methods. This research is a pure experimental laboratory with anode-cathode treatment at different time treatments and voltages. The research device is used factorial device with a pattern 2 x 4. The research results indicate that the motilities and viabilities of dissociation of spermatozoa X and Y with anode-cathode by in Vitro are motilities at 30.33% and viabilities at 67%. Result of spermatozoa Y at the cathode with motilities at 33.25% and viabilities at 65.63%. The best quality of spermatozoa Y dissociation in the cathode was obtained by treatment of voltage 1.0 volt for 10 minutes. Time treatment and voltage do not affect the motilities and viabilities of spermatozoa (P > 0.05).